The Impact of Motivation in Economics Learning toward Social Science Learning Outcomes for High School Students - Mashudi, Mashudi; Alhidayah, Riama; Matsum, Junaidi; Nursiti, Suci (Jurnal Pendidikan Progresif, 2023)
The current research aims to determine the effect of learning motivation as well as economics learning on the social science learning outcomes for high school students in Indonesia. The quantitative explanatory design was applied to the seventy-three social science students at SMAN 1 Kubu, West Kalimantan, Indonesia. Samples were eleventh graders that was chosen purposively. Data was collected through questionnaires, interviews and documentation. Multilinear regression analysis was applied to analyze the relationships between variables. The findings revealed that there exist a simultaneously effect of both motivation and economic learning toward social science learning outcomes (Ftable3.12 and Fcalc=29.82). This research concluded that motivation in economic learning is important predictors to evaluate students’ overall performance in social science learning. Keywords: motivation, economic learning, social science learning outcomes.DOI: http://dx.doi.org/10.23960/jpp.v13.i3.202343